2022
DOI: 10.1186/s12885-022-10274-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between circulating obesity-related biomarkers and prognosis in female breast cancer survivors: a systematic review of observational data in women enrolled in lifestyle intervention trials

Abstract: Obesity plays an important role in the development and progression of breast cancer via various oncogenic pathways. However, the biological mechanisms underlying this relationship are not fully understood. Moreover, it is unclear whether obesity-related and further associated biomarkers could be suitable targets for lifestyle interventions. This systematic review was conducted to examine relationships between obesity-related blood parameters and prognosis for breast cancer survivors enrolled in lifestyle inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Growing evidence suggests that there is a mutual bidirectional association between body fat and inflammation [ 41 ]. Although adiposity promotes the production of inflammatory cytokines, a pro-inflammatory diet can sustain and increase body fat, thereby producing a vicious cycle [ 9 , 20 ]. Our study supports this theory as significantly higher white blood cell and lymphocyte counts across the E-DII tertiles might reflect the ongoing subtle chronic inflammation effect from such a pro-inflammatory diet although the exact mechanism between DII and body fat remains uncertain, it was found that a more pro-inflammatory diet was associated with higher leptin and a lower adiponectin to leptin ratio [ 42 ], and there is a direct association between leptin levels and fat mass in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence suggests that there is a mutual bidirectional association between body fat and inflammation [ 41 ]. Although adiposity promotes the production of inflammatory cytokines, a pro-inflammatory diet can sustain and increase body fat, thereby producing a vicious cycle [ 9 , 20 ]. Our study supports this theory as significantly higher white blood cell and lymphocyte counts across the E-DII tertiles might reflect the ongoing subtle chronic inflammation effect from such a pro-inflammatory diet although the exact mechanism between DII and body fat remains uncertain, it was found that a more pro-inflammatory diet was associated with higher leptin and a lower adiponectin to leptin ratio [ 42 ], and there is a direct association between leptin levels and fat mass in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade chronic inflammation is a hallmark of obesity [ 8 ]. Excess adipose tissue fosters a chronic systemic inflammatory microenvironment by producing a multitude of cytokines and acute-phase proteins such as interleukin-6 and C-reactive protein, which activate pro-inflammatory signalling pathways and prompt tumour development and progression [ 9 ]. Obesity is also linked to white adipose tissue breast inflammation capable of activating the nuclear factor kappa B pathway and the production of oestrogens by the enzyme aromatase, contributing to tumour development and progression [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, lifestyle improvement has a significant impact on BC management after initial diagnosis, both in term of therapeutical efficacy and QoL [ 33 ]. Despite the overall nutritional healthy choices, the maintenance of a normal body weight is mandatory, since it is well documented that obesity is linked to worst outcomes [ 34 , 35 ]. For these reasons, particular attention must be paid to meeting the protein and caloric needs as part of managing weight and body composition, as mentioned before, a crucial aspect of BC treatment.…”
Section: Nutrition and Metabolism In Breast Cancermentioning
confidence: 99%